Prevention of the burnout syndrome in operators of services that attend to people affected by gender-based violence - Deza Villanueva, Sabina (2018)
The professionals who provide care to people affected by gender violence, being in contact with human suffering on a continuous and daily basis, are at risk of being affected by the syndrome of professional exhaustion and related problems, such as vicarious traumatization. and the mobilization of one’s own stories of violence. The impact in the integral health of those professionals, would bring unfavorable implications in the following: work performance, in interpersonal relations in general and in quality of the attention to the victims of violence that come in search of their services, even more, they have tools, strategies and necessary supports in order to perform an effective task. Besides to protect themselves. Considering those aspects in the present article, develops the nature of the concepts: burnout syndrome, healthy work environment and self-care to finally describe some strategies for the creation, implementation and assessment of preventive programs of the SAP.